Renal cell carcinoma in children: case report and literature review - Abdellah, Aissa (Pan Afr Med J, 2015)
Renal cell carcinoma is infrequent in children; consequently it is important to communicate its diagnosis and follow up. The behaviour of this type of tumor is better characterized in adults and in this setting the treatment of choice is surgical resection. However, the place of chemo- and radiotherapy has not been well defined. Here, we present a 9-year-old boy with renal cell carcinoma demonstrating only hematuria without any pathological physical examination findings. The mass was described by abdominal ultrasonography and computed tomography in the left kidney. After the left nephroureterectomy, the patient was given no adjuvant therapy.